Gandan Oral Liquid Improves Exudative Pneumonia by Upregulating Bacteria Clearance via Regulating AQP5 and MUC5AC in Rats. (26th April 2022) - Wang, Yinlong; Yan, Jing; Wang, Peijia; Xu, Xiaoqin
Abstract : Gandan oral liquid (GOL) is a mixture of crude extracts from licorice and Radix isatidis. Clinically, it has been widely used in the treatment of exudative pneumonia (EP) in animals. But the molecular mechanism of these effects is unclear. Therefore, antibacterial activity and therapeutic effect were tested in vitro and in vivo. Exudative pneumonia was established with the intraperitoneal injection of LPS, followed by continuous intranasal inoculation of Klebsiella pneumoniae ( KP ). After that, Gandan oral liquid, acetylcysteine, and levofloxacin were given through the intragastric route for five days, and clinical symptoms were observed and counted. The bacterial content of alveolar lavage fluid was determined, hematology analysis was performed, and lung histology examination was performed. Western blotting, immunohistochemistry, and immunofluorescence were used to detect the expression levels of AQP3, AQP5, and MUC5AC in lung tissues. ELISA kit was used to detect serum and BALF cytokines levels. The results showed that GOL (242 mg/mL) had no antibacterial activity on Klebsiella pneumonia ( KP ), and the effect was significantly worse than levofloxacin. However, the therapeutic test in vivo of the rat model of bacterial EP showed different results. After treatment, GOL administration ameliorated EP and increased the expression of mucoprotein -5AC (MUC5AC), and GOL promoted water secretion of the respiratory tract by increasing the expression of aquaporin-5 (AQP5) and decreasing the levels of proinflammatory cytokines (TNF- α, IL-6, and IL-1 β ). Conclusion . GOL accelerates the water secretion of respiratory tract, inhibits the inflammatory response, induces removal of bacteria of respiratory tract via the AQPs/MUC pathway, and ultimately ameliorates EP.